Modeling of Bound Electron Effects in Particle-in-Cell Simulation (Communications in Computational Physics, 2022)
To include the bound electron effects in particle-in-cell (PIC) simulation, wepropose a model in which the response of the dipole components of partially ionizedions to external electromagnetic fields can be included. Instead of treating the macroion particle as a single particle without an internal structure, the ions are consideredto have a structure composed of a central nucleus and a bounded electron cloud inour model. The two parts experience the interactions of both the external electromagnetic fields and the internal Coulomb fields. In this way, the laser scattering effectsby a partially ionized medium can be modeled properly in the PIC simulation. Thelaser propagation in a neutral medium and the Bragg scattering of the laser in crystal structure have been simulated with a PIC code modified based on our model asthe benchmark. Our model may find applications to study some interesting problems,such as the x-ray laser-driven wakefield acceleration in crystals, the x-ray laser-drivenhigh energy density physics, and intense laser propagation in partially ionized nonlinear optical materials, etc.